2004
DOI: 10.1017/cbo9780511790973
|View full text |Cite
|
Sign up to set email alerts
|

Muslims and the State in Britain, France, and Germany

Abstract: Over ten million Muslims live in Western Europe. Since the early 1990s, and especially after the terrorist attacks of September 11, 2001, vexing policy questions have emerged about the religious rights of native-born and immigrant Muslims. Britain has struggled over whether to give state funding to private Islamic schools. France has been convulsed over Muslim teenagers wearing the hijab in public schools. Germany has debated whether to grant 'public-corporation' status to Muslims. And each state is searching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(42 citation statements)
references
References 80 publications
3
39
0
Order By: Relevance
“…There is no doubt that existing approaches to and forms of religious education in Western liberal democracies vary historically, crossnationally, and intra-nationally. These variations reflect the different patterns of historical church-state and church-state-and-school relations in democratic societies (Monsma & Soper, 1997); prevalent models for regulating religion in the public sphere, including in education (Richardson, 2004;Plesner, 2005a); and country-specific historical trajectories and institutional arrangements for integrating religious minorities (Fetzer & Soper, 2005). In the US, the First Amendment to the Constitution and the country's strict separation of church and state placed religious education beyond the scope of public education.…”
Section: Liberal Democratic Consensus In Religious Educationmentioning
confidence: 99%
“…There is no doubt that existing approaches to and forms of religious education in Western liberal democracies vary historically, crossnationally, and intra-nationally. These variations reflect the different patterns of historical church-state and church-state-and-school relations in democratic societies (Monsma & Soper, 1997); prevalent models for regulating religion in the public sphere, including in education (Richardson, 2004;Plesner, 2005a); and country-specific historical trajectories and institutional arrangements for integrating religious minorities (Fetzer & Soper, 2005). In the US, the First Amendment to the Constitution and the country's strict separation of church and state placed religious education beyond the scope of public education.…”
Section: Liberal Democratic Consensus In Religious Educationmentioning
confidence: 99%
“…On the other hand, Alexander and Welzel found that in both predominantly Muslim and non-Muslim societies, self-identifying Muslims show higher prevalence of support for patriarchal values than non-Muslims (2011). This comports with studies showing persistent support for traditional values among Muslim immigrants in non-Muslim nations (Buijs and Rath 2002;Fetzer and Soper 2005). Thus, much of the academic work suggests that Muslims support democratic political values but seek to maintain traditional social structures Mogahed 2007, 2008), though there are variations on theories explaining why these preferences exist.…”
Section: Introductionmentioning
confidence: 53%
“…Thet ime elapsed from the recognition of Islam to the implementation of that recognition is largely due to the wide diversity of Muslim communities and the mutualdistrust between these communities and the government. As in other countries (Fetzer /Soper 2005;Husson /Dury 2006;Potz /Wieshaider 2004), the Belgian authorities have been confronted with the difficulty of identifying a representative and uncontestedinterlocutorfor the variousMuslim communities.…”
Section: The Recognition Of Islammentioning
confidence: 99%